2022
DOI: 10.1101/2022.12.06.519405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using light for energy: examining the evolution of phototrophic metabolism through synthetic construction

Abstract: Evolutionary innovations helped transform life on Earth. The origin of phototrophy was pivotal to increasing biomass, by utilizing light-driven energy transport to drive biological processes. Retinalophototrophy constitutes one of two phototrophic pathways on Earth, consisting of a simple system of microbial rhodopsins which are exemplars of horizontal gene transfer. Here, we seek to determine if Saccharomyces cerevisiae, a heterotrophic fungus, can function as a facultative artificial phototroph after acquiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…In previous studies, increases in intracellular ATP supply were achieved by expressing dR in the mitochondria of eukaryotic cells, such as mammalian cells [ 8 ] and Drosophila [ 9 ]. A trial of the expression of rhodopsin in the vacuoles of S. cerevisiae was preliminarily reported in a patent in 2021 [ 17 ] and a preprint in 2023 [ 18 ]; however, the effect of this expression in vacuoles and cellular energetic metabolism has not been reported previously. This study is the first report describing the direct measurement of light-driven proton pumping activity from isolated vacuoles expressing bacterial rhodopsin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, increases in intracellular ATP supply were achieved by expressing dR in the mitochondria of eukaryotic cells, such as mammalian cells [ 8 ] and Drosophila [ 9 ]. A trial of the expression of rhodopsin in the vacuoles of S. cerevisiae was preliminarily reported in a patent in 2021 [ 17 ] and a preprint in 2023 [ 18 ]; however, the effect of this expression in vacuoles and cellular energetic metabolism has not been reported previously. This study is the first report describing the direct measurement of light-driven proton pumping activity from isolated vacuoles expressing bacterial rhodopsin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Burnetti and Ratcliff collaboratively engineered S. cerevisiae into a facultative phototroph by introducing a rhodopsin protein from Ustilago maydis into the vacuole, enabling light-driven proton pumping into the vacuolar compartment without consuming ATP. The findings demonstrated that the yeast engineered with rhodopsins exhibit a selective growth advantage under green light, displaying faster growth rates than their nonphototrophic ancestor and rhodopsin-expressing yeast grown in the dark [ 82 ]. To convert CO 2 into value-added compounds continuously, Erb and coworkers [ 83 ] created a modular platform for continuously converting CO 2 to acetyl- and malonyl-CoA that were converted into monoterpenes, sesquiterpenes, and polyketides via the use of varied terpene and polyketide synthases.…”
Section: Engineering Artificial Biological Systems For C1 Utilizationmentioning
confidence: 99%